2002
DOI: 10.1038/sj.bjc.6600622
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma-like vascular density in atypic keratoacanthoma suggests malignant progression

Abstract: Differential diagnosis between keratoacanthomas and well differentiated squamous cell carcinomas based on clinical and histomorphological data is problematic. Recent findings of cellular atypia in a large proportion of keratoacanthomas indicated that these potentially 'self-healing' cutaneous neoplasms had the potential for malignant progression. Another malignancyassociated criterion is enhanced angiogenesis with increased microvessel density. To provide further diagnostic markers for keratoacanthomas we exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
0
7
0
2
Order By: Relevance
“…It has been showed that increasing of reactive oxygen and nitrogen species could also induce expression of a variety of cancer associated gens including the tumor necrosis factor gene (TNF), matrix metalloproteinases (MMP) genes, and vascular endothelial growth factor (VEGF) genes. Up regulation of these genes could affect on cell migration and angiogenesis via regulation of Nuclear Factor ĸB (NFĸB) …”
Section: Introductionmentioning
confidence: 99%
“…It has been showed that increasing of reactive oxygen and nitrogen species could also induce expression of a variety of cancer associated gens including the tumor necrosis factor gene (TNF), matrix metalloproteinases (MMP) genes, and vascular endothelial growth factor (VEGF) genes. Up regulation of these genes could affect on cell migration and angiogenesis via regulation of Nuclear Factor ĸB (NFĸB) …”
Section: Introductionmentioning
confidence: 99%
“…The real nature of this neoplasma and its relationship to squamous cell carcinoma (SCC) have been disputed for a long time. Some authors consider KA as a benign neoplasia, others as a precursor of SCC, 2 others as a well-differentiated variant of cutaneous SCCs 3 or at least an abortive malignancy that only rarely progresses into an invasive SCC. 4 Differential diagnosis between KA and SCC is challenging due to their similarities and the lack of reliable diagnostic criteria to distinguish both entities.…”
Section: Introductionmentioning
confidence: 99%
“…4 It is thought that those keratoacanthomas of sun-exposed locations and diagnosed in older patients may more frequently progress to SCC. 5 Some authors believe that keratoacanthoma is a well-differentiated variant of SCC representing a range of neoplastic activity with no clear distinction, whereas some authors consider the histological and cytological differentiation precise, sure, and possible. 1,[5][6][7] Thus, the natural behavior of keratoacanthomas remains unclear and controversial, and practically all these tumors are currently surgically excised.…”
mentioning
confidence: 99%
“…5 Some authors believe that keratoacanthoma is a well-differentiated variant of SCC representing a range of neoplastic activity with no clear distinction, whereas some authors consider the histological and cytological differentiation precise, sure, and possible. 1,[5][6][7] Thus, the natural behavior of keratoacanthomas remains unclear and controversial, and practically all these tumors are currently surgically excised. 3 In addition to the proportion of cells with atypia, one malignancy-associated criterion in keratoacanthomas is increased microvessel density.…”
mentioning
confidence: 99%
See 1 more Smart Citation